Anthropological Analysis of Literature and Local Wisdom in the Novel KKN Desa Penari by Simpleman - Enny Rahayu; Helisda Pratiwi (Proceeding International Conference on Malay Identity, 2021)
Abstract: This study aims to describe the moral values ??in the KKN novel in Desa Penari by Simpleman. The data source for this research is the novel KKN in the Penari Village by Simpleman which has 260 pages published by PT Bukune Kreatif Cipta, printed second in October 2019. The research data is the moral values ??in the KKN Desa Penari Karya Simpleman novel. This research method uses descriptive methods by collecting data, describing data, and analyzing data. The instrument used in this study was a documentation guide. The data analysis technique used was reading the novel repeatedly, internalizing, understanding, collecting data, underlining, describing, and concluding the results of the research. The results of the study found moral values ??which consist of values the moral relationship between humans and God, the relationship between humans and oneself, and the relationship between humans and humans. Keywords: Moral Values, Novels, Simpleman's KKN Desa Penari